Towards John Protevi, Political Affect: Connecting the Social and the Somatic - Stojanovski, Igor (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Igor Stojanovski Title (English): Towards John Protevi, Political Affect: Connecting the Social and the Somatic Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 149-151 Page Count: 3 Citation (English): Igor Stojanovski, “Towards John Protevi, Political Affect: Connecting the Social and the Somatic,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011): 149-151.